New atheism: genesis and formation - Bezniuk, Dmitry K. (Journal of the Belarusian State University. Sociology, 2023)
The author of the article refers to the phenomenon of new atheism, which is a form of modern free-thinking and has many supporters in the Western intellectual tradition. Attention is drawn to the fact that the reason for the entry of new atheism into the cultural arena was the terrorist attacks of 2001 September 11 in the United States of America with the participation of Islamic extremists, which drew attention to the problem of religious motivation in the thinking and behaviour of modern man. The article attempts to identify and clarify the causes of the new atheism and the factors that contributed to its formation. The author draws attention to the intellectual, theoretical and methodological conditions for the emergence of the new atheism (the tradition of atheism and freethinking in American and European cultures, philosophical and psychological teachings of the 18–20th centuries) and the specific historical conditions under which the new atheism began its ascent (the influence of Protestant groups in the political life of the USA, postmodern culture, migration processes, the consequences of secularisation, etc.).
Keywords: religion; new atheism; criticism; factors; conditions; religious faith; war; creationism; extremism